2002
DOI: 10.1108/09513570210440568
|View full text |Cite
|
Sign up to set email alerts
|

Corporate annual reports: research perspectives used

Abstract: Corporate annual reports are viewed through the lens of researchers of these documents. The aims are to obtain insight into how researchers view annual reports; to ascertain how the different ways of seeing the annual report relate to each other; and to draw out the gaps in this diverse research in a continuing attempt to understand its role and purpose. Selective examination of a decade of corporate annual report research (1990‐2000) reveals how researchers have sought to find visibility and meaning. Few stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
172
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(178 citation statements)
references
References 11 publications
3
172
0
3
Order By: Relevance
“…Poorperforming companies had limited accomplishments to refer to and instead used the credentials of board members as an assurance to shareholders that the company's strategy could be entrusted to them. Findings supported previous studies (Abrahamson & Park, 1994;Bournois & Point, 2006;Stanton & Stanton, 2002), which suggested that high-performing companies are more inclined to take credit for high performance, while bad results in poor-performing companies are often attributed to the unfavourable economic climate.…”
Section: Performancesupporting
confidence: 80%
See 1 more Smart Citation
“…Poorperforming companies had limited accomplishments to refer to and instead used the credentials of board members as an assurance to shareholders that the company's strategy could be entrusted to them. Findings supported previous studies (Abrahamson & Park, 1994;Bournois & Point, 2006;Stanton & Stanton, 2002), which suggested that high-performing companies are more inclined to take credit for high performance, while bad results in poor-performing companies are often attributed to the unfavourable economic climate.…”
Section: Performancesupporting
confidence: 80%
“…Researchers generally view annual reports as a tool used by management to construct a picture of how it would like to be viewed in the eyes of institutional investors, as well as other relevant stakeholders (MerklDavies & Koller, 2012;Smith, Dong & Ren, 2011;Stanton & Stanton, 2002). The importance of annual reports is that they are information-dispensing tools that communicate the personality and philosophy of the company, as well as marketing tools that can impart a particular organisational message (Stanton & Stanton, 2002: 478).…”
Section: Inclusion Of Integrated Reporting Content Elements In Narratmentioning
confidence: 99%
“…Annual report narratives are effective means to communicate such messages as they convey particular meanings and outcomes (Stanton and Stanton, 2002) and respond to pressure from the public and policy makers (Walden and Schwartz, 1997). If a public policy adversely affects certain stakeholders, but remains attractive to a private-sector organisation, managers have incentives to engage in impression management to influence and shape users' perceptions of the private-sector organisation and/or the public policy.…”
Section: Introductionmentioning
confidence: 99%
“…The annual report (AR) can be a good option to use, as it is updated on an annual basis, tends to use simple language to explain all the facts and figures, and can be downloaded from the net or requested from the companies themselves. Additionally, they are interesting texts to analyze, as their authors have to be frank and offer true facts and figures, a basic aspect of this type of texts for many years (see for instance, Lentz & Tshirgi 1963, on the ethical content of the annual reports, something also observed by Stanton & Stanton 2002). Furthermore, this text also adopts a consumer focus, meeting the information needs of investors and creditors in such a way that could embrace a "broader, integrated range of information" (AICPA 1994, 131).…”
Section: Materials In the English For Business Communication Classroommentioning
confidence: 99%